CRIME AND VICTIMIZATION ISSUES IN CONTEMPORARY GEORGIA - Glonti, Georgi (European Scientific Journal, ESJ, 2015)
The author analyzes the results of the four stages of victimization surveys and Unified Crime Reports prepared by the Ministry of Internal Affairs of Georgia in 2010-2013. The results of victimization surveys and statistics reports related to indexes and structure of crime became important after the parliamentary elections held in October 1, 2012, resulted by defeating of the ruling political party “National Movement” which was in power for the last 9 years. The new coalition “Georgian Dream”, headed by the billionaire B. Ivanishvili, radically changed political climate and announced the acceleration of democratization of the country and adopted the legislation decriminalization policy. According the new policy, the government of the country carried out the general amnesty, and released more than 60% of all prisoners from the custody. Such policy became the object of serious criticism from the part of the oppositions and some experts. They have expressed concerns about the criminal situation and decreasing level of security in the country predicted anarchy and disorganizations. This article is an attempt to assess the real situation in Georgia and the level of real threat to stability posed by criminality.